Newly Appointed CRCCs in Koraput District of Odisha Perceptions, Problems and Promises - Pradhan, Manoranjan; Bagarti, Chandrakala (JOURNAL OF INDIAN EDUCATION, 2016)
Educational status in tribal and rural pockets of Odisha, in terms of literacy or enrolment, retention, participation and achievement in different stages of education, are not at par with national level. Particularly in tribal Odisha, low literacy rate, comparatively high dropout rate, low learning achievements of students, poor infrastructural facilities in schools, inadequate number of teachers as per RTE norm, language difficulties, etc. still remain as major challenges. Recently, 101 Cluster Resource Centre Coordinators (CRCCs) in 13 blocks were appointed for looking after the elementary education in Koraput, a tribal dominated district of Odisha. The present paper is an attempt to know the visions of the newly recruited CRCCs about their new assignments. To know the status of different clusters from the newly recruited CRCCs, a selfprepared questionnaire was administered and data were analysed following descriptive method. It is expected that the paper will help the policy makers to think seriously about the education of children in tribal and rural areas as per suggestions given by the newly recruited CRCCs from their experiences as teachers of these areas for not less than ten years.